The Social Nature of Emotions - Agneta H. Fischer (Frontiers Research Topics, 2016)
Emotion is a defining aspect of the human condition. Emotions pervade our social and professional lives, they affect our thinking and behavior, and they profoundly shape our relationships and social interactions. Emotions have traditionally been conceptualized and studied as individual phenomena, with research focusing on cognitive and expressive components and on physiological and neurological processes underlying emotional reactions. Over the last two decades, however, an increasing scholarly awareness has emerged that emotions are inherently social - that is, they tend to be elicited by other people, expressed at other people, and regulated to influence other people or to comply with social norms (Fischer & Manstead, 2008; Keltner & Haidt, 1999; Parkinson, 1996; Van Kleef, 2009). Despite this increasing awareness, the inclusion of the social dimension as a fundamental element in emotion research is still in its infancy (Fischer & Van Kleef, 2010). We therefore organized this special Research Topic on the social nature of emotions to review the state of the art in research and methodology and to stimulate theorizing and future research. The emerging field of research into the social nature of emotions has focused on three broad sets of questions. The first set of questions pertains to how social-contextual factors shape the experience, regulation, and expression of emotions. Studies have shown, for instance, that the social context influences the emotions people feel and express (Clark, Fitness, & Brissette, 2004; Doosje, Branscombe, Spears, & Manstead, 2004; Fischer & Evers, 2011). The second set of questions concerns social-contextual influences on the recognition and interpretation of emotional expressions. Studies have shown that facial expressions are interpreted quite differently depending on the social context (e.g., in terms of status, culture, or gender) in which they are expressed (Elfenbein & Ambady, 2002; Hess & Fischer, 2013; Mesquita & Markus, 2004; Tiedens, 2001). The third set of questions has to do with the ways in which people respond to the emotional expressions of others, and how such responses are shaped by the social context. Studies have shown that emotional expressions can influence the behavior of others, for instance in group settings (Barsade, 2002; Cheshin, Rafaeli & Bos, 2011; Heerdink, Van Kleef, Homan, & Fischer, 2013), negotiations (Sinaceur & Tiedens, 2006; Van Kleef, De Dreu, & Manstead, 2004), and leadership (Sy, Côté, & Saavedra, 2005; Van Kleef, Homan, Beersma, & Van Knippenberg, 2010). This Research Topic centers around these and related questions regarding the social nature of emotions, thereby highlighting new research opportunities and guiding future directions in the field. We bring together a collection of papers to provide an encyclopedic, open-access snapshot of the current state of the art of theorizing and research on the social nature of emotion. The state of the art work that is presented in this e-book helps advance the understanding of the social nature of emotions. It brings together the latest cutting-edge findings and thoughts on this central topic in emotion science, as it heads toward the next frontier.